Penerapan Model PJBL (Project Based Learning) melalui Media Permainan Ular Tangga dalam Pembelajaran Menulis Surat Pribadi pada Siswa Kelas VII SMP Plus Ja-Alhaq Kota Bengkulu - Kelaudia Utami, Sindi; Kasmantoni; Friantary, Heny (Universitas Al-Qolam Malang, 2025)
This study aims to describe the implementation of the Project Based Learning (PJBL) model through the snakes and ladders game media in learning to write personal letters to class VII students of SMP Plus Ja-alhaq, Bengkulu City. This study uses a qualitative approach with a descriptive method. The subjects of the study were teachers and class VII students. Data collection techniques were carried out through interviews, observations, and documentation. The results of the study indicate that the implementation of the PJBL model through the snakes and ladders game media can increase students' motivation, activeness, and writing skills. The snakes and ladders media that are designed interactively and attractively make the learning process more enjoyable, foster creativity, and strengthen cooperation between students. The obstacles faced such as time constraints and student adaptation to new media can be overcome with good time management and teacher direction. In conclusion, the implementation of PJBL assisted by the snakes and ladders game media is effective in improving the ability to write personal letters to class VII students of SMP Plus Ja-alhaq, Bengkulu City.